Relevance of Local Dispersion on Mixing Enhancement in Engineering Injection and Extraction Systems in Porous Media: Insights from Laboratory Bench-Scale Experiments and Modeling - Ziliotto, Francesca; Basilio Hazas, Mónica; Muhr, Markus; Ahmadi, Navid; Rolle, Massimo; Chiogna, Gabriele (Transport in Porous Media, 2025)
This work investigates the dynamics of flow, transport and mixing in subsurface porous media during an engineered injection–extraction (EIE) system. We perform laboratory bench-scale experiments mimicking an EIE system in an unconfined aquifer, and we explore the role of local dispersion on mixing enhancement. The experimental setup is equipped with four wells operated in a sequence, one at a time, creating transient flows and a fluctuating water table impacting the transport dynamics of an injected dye tracer plume. A high-resolution imaging technique is applied to monitor the spatial and temporal evolution of the plume concentration. The experiments are performed in porous media with fine and coarse grain sizes and considering two different sequences of injection and extraction. The plume spreading and mixing are quantified by computing the spatial moments and the plume area, respectively. The Okubo–Weiss parameter is calculated over the plume area to correlate mixing enhancement with changes in flow topology. The results indicate that the operation of EIE system significantly enhances mixing and spreading, particularly when the effective Okubo–Weiss parameter is higher. Furthermore, the mixing enhancement is larger in the experiments performed in the coarse porous media, indicating the importance of local dispersion as a factor for mixing enhancement in EIE systems.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Engineered injection–extraction system; Flow topology; Local dispersion; Mixing